Integrative transcriptomic analysis deciphering the role of rice bHLH transcription factor Os04g0301500 in mediating responses to biotic and abiotic stresses - Zhang, Qiuping; Teng, Rong; Yuan, Ziyi; Sheng, Song; Xiao, Yunhua; Deng, Huabing; Tang, Wenbang; Wang, Feng (Frontiers in Plant Science, 2023)
Understanding the signaling pathways activated in response to these combined stresses and their crosstalk is crucial to breeding crop varieties with dual or multiple tolerances. However, most studies to date have predominantly focused on individual stress factors, leaving a significant gap in understanding plant responses to combined biotic and abiotic stresses. In this study, we identify 106OsbHLHs by multi-step homolog search. Phylogenic analysis, molecular weights, isoelectric points, and conserved domain screening were processed. Following, integrative transcriptome analysis using 6 RNA-seq data including Xoo infection, heat, and cold stress was processed. Initially, we identified Os04g0301500 and Os04g0489600 as potential negative regulators of Xoo resistance in rice. The expression of Os04g0301500 under different temperature conditions and Xoo infection is further investigated, revealing potential crosstalk with temperature signaling pathways. In addition, we also cross-validate that Os04g0301500 is involved in non-freezing temperatures (around 4℃) but not to 10℃ cold stresses, suggesting a complex interplay with temperature signaling pathways. The study concludes that Os04g0301500 may play a crucial role in integrating biotic and abiotic stress responses in rice, potentially serving as a key regulator of plant resilience under changing environmental conditions, which could be important for further multiple stresses enhancement and molecular breeding through genetic engineering in rice.